A Low-Profile Patch-Loaded Ring Antenna With Wide Frequency Tuning Capability for Dual-Band Metal-Mountable Tag Design - Muthukannan Murugesh; Sharul Kamal Abdul Rahim; Eng Hock Lim; Pei Song Chee (IEEE Access)
A low-profile, dual-band tag antenna (39 mm $× 39$ mm $× 1.38$ mm), which is loaded with a circular patch at the central region for frequency tuning purposes, has been proposed for on-metal applications that operate in the Lower European (LEu) and the North American (NA) UHF-RFID passbands. The antenna itself consists of a square ring as well as a hexagonal ring, all of which can be fully made on a single-layer substrate, and they are concentrically stacked for generating a stable broadside radiation pattern on metal surface. The dimensions of the rings can be adjusted to achieve efficient wide-range frequency tuning capability, with conjugate impedance matching over the two operating frequencies. The proposed tag antenna is simple, and it does not require the use of other complex tuning mechanisms. Independent frequency tuning is possible over the two passbands. With 4W Effective Isotropic Radiated Power (EIRP), the maximum measured realized gain is −5.69 dBi at 868 MHz in the LEu UHF RFID band while −5.18 dBi at 921 MHz in the NA UHF RFID band. This configuration enables extended read ranges of 8 m and 9 m for the LEu and NA UHF RFID passbands, respectively. A detailed analysis was conducted to understand the resonance characteristics, and a Transmission Line (TL) model was constructed to facilitate the design of the tag antenna. It is important to highlight that the two tag resonant frequencies are stable and not much affected by the presence of the backing metallic object. Dual-band UHF RFID tags are useful for cross-national tracking and identification applications, where their systems may be operating in two different passbands without compatibility.